Zasnova participativnega načrtovanja - Bončina, Andrej (Gozdarski vestnik, 2004)
The article presents the fundamental characteristics of participatory planning. Participation of the public in the planning process implies a larger concern for the interests of the public and possibly its active participation in the planning processes as well as improved public supervision of decision makers. There are various forms of participation and the choice of individual forms depends on the actual circumstances and the envisaged degree of public involvement in the planning process. The authors draw attention to the advantages and disadvantages of participatory processes in forestry planning, present some foreign experience in involving the public in forestry planning and propose step-by-step introduction of certain participatory processes into the Slovenian concept of forest management planning.
Keywords: gozdno gospodarstvo; gozdnogospodarski načrti; javni interes; participativni management